2018
DOI: 10.1186/s40795-017-0207-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D supplementation on C-reactive protein; a systematic review and meta-analysis of randomized controlled trials

Abstract: Background: To evaluate the effect of vitamin D supplementation on C-reactive protein (CRP) through a systematic review and meta-analysis of randomized control trials (RCTs). Methods: PubMed-Medline, SCOPUS, Google Scholar and Web of Science databases were searched (up until April 2016) to identify RCTs evaluating the impact of vitamin D supplementation on CRP. We used random effects models (using DerSimonian-Laird method) as well as the generic inverse variance methods for quantitative data synthesis. For sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 48 publications
4
38
2
Order By: Relevance
“…In Ethiopia, a high national prevalence of Zn deficiency has been estimated previously based on Zn supplies in the food system, which reported that 81% of the population were at risk of deficiency due to inadequate dietary Zn supplies, estimated from food balance sheets and regional food composition data 11 . A high prevalence of Zn deficiency (> 20%) has also been reported based on serum Zn status and dietary Zn intake among young children and school-aged children 13 , 34 36 and women and pregnant women 12 , 37 , 38 . Several factors may contribute to a high prevalence of Zn deficiency in Ethiopia, where the consumption of Zn-rich foods such as meat is low 39 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In Ethiopia, a high national prevalence of Zn deficiency has been estimated previously based on Zn supplies in the food system, which reported that 81% of the population were at risk of deficiency due to inadequate dietary Zn supplies, estimated from food balance sheets and regional food composition data 11 . A high prevalence of Zn deficiency (> 20%) has also been reported based on serum Zn status and dietary Zn intake among young children and school-aged children 13 , 34 36 and women and pregnant women 12 , 37 , 38 . Several factors may contribute to a high prevalence of Zn deficiency in Ethiopia, where the consumption of Zn-rich foods such as meat is low 39 .…”
Section: Discussionmentioning
confidence: 96%
“…This high prevalence of Zn deficiency is consistent with reports of low dietary Zn intake. For example, Girmay et al reported that the mean dietary Zn intake among children 6–35 months (n = 6,752) was 1.74 mg day −1 at national level 13 , which is small compared to an Estimated Average Requirement (EAR) of 2.5 mg day −1 . Furthermore, the phytate contents of Ethiopian diets are high which is likely to inhibit Zn absorption 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that PTH may cause insulin resistance by reducing glucose uptake by the liver, muscle, and adipose cells [51]. A recent study revealed that vitamin D supplementation has no effect on CRP, interleukin-10, or tumor necrosis factor-α concentrations [52].…”
Section: Discussionmentioning
confidence: 99%
“…This study correlated the low serum level of vitamin D with a higher C-reactive protein (CRP) level in COVID-19 patients based on previous findings (85,86). In fact, multiple observational and intervention studies have suggested the beneficial effects of vitamin D on reducing circulating CRP and pro-inflammatory cytokines (86)(87)(88)(89)(90). This has a beneficial impact in lowering a heightened inflammation state that is associated with poorer outcomes (91)(92)(93).…”
Section: Vitamin D Prevents the Maladaptive Cycle Of Local Inflammatimentioning
confidence: 90%